Infra-Inguinal Aneurysms - Threat to Life and Limb? - Moussa O; Mittapalli D; Suttie SA (International Journal of Vascular Surgery and Medicine - Peertechz Publications, 2016)
Objectives: To assess the outcomes of infra-inguinal aneurysms admitted to a regional vascular unit. Methods: All patients admitted with a primary diagnosis of infra inguinal aneurysms were identified from clinical coding lists over a four-year period (January 2008-May 2012). All patients were identified through clinical coding and records were checked to confirm diagnosis, management and outcome, with data analysed using SPSS v18. Results: 39 patients (mean age 58.3yr, range 18-98), of which 27 were male, were identified (24 PseudoAneurysms (PA), 12 True Aneurysms (TA) and 3 Mycotic Aneurysms (MA)). The majority of the PAs were secondary to Intravenous Drug Abuse, IVDA (41%), followed by interventional procedures (29%), vascular anastomotic sites (13%), orthopaedic surgery (13%) and penetrating trauma (4%). 11/12 (92%) TAs were popliteal in origin, with 22/24 (92%) of PAs located at or around the femoral bifurcation. 22/24 of PA (12 surgical; 4 endovascular stenting; 1 ultrasound guided thrombin injection; 4 ultrasound guided compression; 1 embolisation), 8/12 of TA (7 surgical; 1 endovascular stenting) and 3/3 MA (2 surgical; 1 combined surgical + endovascular stenting) required intervention. One patient underwent primary major amputation (popliteal TA) with a further three patients requiring major amputation post intervention (1 MA post bypass procedure, 1 PA post vessel ligation, 1 PA secondary to percutaneous intervention presenting with distal embolization requiring vessel ligation). Overall 30-day mortality was 5.1% (n=2). Conclusions: Our results suggest that the risk of major amputation and mortality secondary to infra-inguinal aneurysms as a pathology is significant.